Ticks and hemoplasma screening in dromedary camels (Camelus dromedarius) from Somalia - Collere, Flávia C M; Ferrari, Larissa D R; Osman, Aamir M.; Hassan-Kadle, Ahmed A.; Shair, Mohamed A.; Coradi, Vanessa S.; Ibrahim, Abdalla M.; Martins, Thiago F.; Yusuf, Abdulkarim A.; de Barros-Filho, Ivan R.; Lange, Rogério R; André, Marcos R. [UNESP]; et al. (Oxford University Press (OUP), 2025)
Hemotropic mycoplasmas (hemoplasmas) are small pleomorphic bacteria that parasitize the surface of red blood cells of mammals. Hemoplasmas have been described in different species from the Camelidae Family, such as llamas and alpacas (South American camelids), but data on dromedary camels (Camelus dromedarius) are limited to a few reports. Somalia has one of the world's largest dromedary camel populations, and studies on hemoplasmas and tick-borne pathogens are lacking. Accordingly, this study aimed to screen dromedaries from Somalia for hemoplasmas by PCR-based assays. A total of 155 dromedary camel blood samples from 2 different areas of Mogadishu (n = 104) and the Lower Shabelle Region (n = 51) of the country were collected. All blood DNA samples were screened for hemoplasmas using a SYBR Green Universal Real-Time PCR (qPCR), nested PCR (nPCR), and conventional PCR (cPCR) assays targeting the 16S rRNA gene of hemoplasmas. Five out of 155 animals (3.23%; 95% confidence interval [CI]: 1.39-7.33%) were positive for hemoplasmas. A total of 346 (228 M, 117 F, and 1 nymph) ticks were collected from 79/155 (50.9%; 95% CI: 42.8-59.1%) dromedary camels with a mean of 4.4 ticks per animal. Ticks were identified as Rhipicephalus pulchellus (174/346; 50.3%), Hyalomma dromedarii (103/346; 29.8%), Hyalomma rufipes (35/346; 10.1%), Hyalomma marginatum (16/346; 4.6%), Rhipicephalus humeralis (14/346; 4.0%), Amblyomma lepidum (2/346; 0.6%), Amblyomma gemma (1/346; 0.3%), and Ornithodoros sp. (1/185; 0.5). This is the first study on the molecular screening for hemoplasmas in dromedary camels from Somalia and the first report of A. lepidum and R. humeralis in Somali dromedary camels.
Keywords: hemotropic mycoplasma; Sub-Saharan Africa; tick